MODELING ON THE COMPUTER OF RADIATION DEFECTS IN THE TITAN, IRRADIATED BY LIGHT IONS - Togambayeva, A. K.; Комаров, Ф. Ф.; Kupchishin, A. I.; Shmygaleva, T. A. (Recent Contributions to Physics, 2009)
The work is devoted to modeling on the computer of radiation defects generation processes in the titan irradiated by light ions, within the limits of an in cascade-probabilistic method. Algorithms and complex of programs for calculation of spectra of the primarily-knocked out atoms and concentration of radiation defects in the solid irradiated by ions, in the environment C++ Builder are developed. Calculations are made for various flying particles and titan target. Regularities of the area of result CPF and concentration of radiation defects are received at an ion irradiation for various flying particles.
Keywords: light ions